The effects of familiarization on intelligibility and lexical segmentation in hypokinetic and ataxic dysarthria - Liss, Julie M. (2002)
This study is the third in a series that has explored the source of intelligibility decrement in dysarthria by jointly considering signal characteristics and the cognitive–perceptual processes employed by listeners. A paradigm of lexical boundary error analysis was used to examine this interface by manipulating listener constraints with a brief familiarization procedure. If familiarization allows listeners to extract relevant segmental and suprasegmental information from dysarthric speech, they should obtain higher intelligibility scores than nonfamiliarized listeners, and their lexical boundary error patterns should approximate those obtained in misperceptions of normal speech. Listeners transcribed phrases produced by speakers with either hypokinetic or ataxic dysarthria after being familiarized with other phrases produced by these speakers. Data were compared to those of nonfamiliarized listeners [Liss et al., J. Acoust. Soc. Am. 107, 3415–3424 (2000)]. The familiarized groups obtained higher intelligibility scores than nonfamiliarized groups, and the effects were greater when the dysarthria type of the familiarization procedure matched the dysarthria type of the transcription task. Remarkably, no differences in lexical boundary error patterns were discovered between the familiarized and nonfamiliarized groups. Transcribers of the ataxic speech appeared to have difficulty distinguishing strong and weak syllables in spite of the familiarization. Results suggest that intelligibility decrements arise from the perceptual challenges posed by the degraded segmental and suprasegmental aspects of the signal, but that this type of familiarization process may differentially facilitate mapping segmental information onto existing phonological categories.